13 Deep vein thrombosis after acute achilles tendon rupture. An RCT comparing early controlled motion of the ankle with no motion. (April 2019) - Barfod, Kristoffer Weisskirchner; Nielsen, Emil; Hærsted Olsen, Beth; Gustavo Vinicoff, Pablo; Troelsen, Anders; Holmich, Per
Abstract : Background: Deep vein thrombosis (DVT) following acute Achilles tendon rupture (ATR) is common (up to 34%) and potentially dangerous. Immobilization (IM) is thought to be an important factor in the pathogenesis. Purpose of the study: To investigate if early controlled ankle motion ECM could reduce the incidence of DVT compared to IM in the treatment of acute Achilles tendon rupture. Materials and methods: The study was performed as a randomized controlled trial. Patients aged 18 to 70 years were eligible for inclusion. Treatment was non-operative. The ECM group performed movements of the ankle 5 times a day from week 3 to 8 after rupture. The control group was IM for 8 weeks. Follow up was performed with Color Doppler ultrasound at 2 and 8 weeks by two experienced radiologists. DVT was a secondary outcome, why a secondary power calculation was performed: 124 patients were required to have a 60% chance of detecting, as significant at the 5% level, a decrease in DVT from 34% in the IM group to 17% in the ECM group. Findings/results: 189 patients were assessed for eligibility and 130 randomized: 68 (ECM-group) and 62 (IM-group). All patients participated in the follow up. 62 (47.7%) patients were diagnosed with DVT; 34/69 (49.3%) in the ECM group and 28/61 (45.9%) in the IM group (p=0.70). Conclusions: The incidence of asymptomatic DVT was higher than previously reported as 48% presented with DVT. ECM revealed no benefit to IM in reducing the incidence of DVT.